Drug-induced psoriasis: clinical perspectives - Balak DMW; Hajdarbegovic E (Dove Medical Press, 2017)
Deepak MW Balak, Enes Hajdarbegovic Department of Dermatology, Erasmus University Medical Center, Rotterdam, the Netherlands Abstract: Exposure to certain drugs can elicit an induction or exacerbation of psoriasis. Although well-conducted systematic studies on drug-related psoriasis are mostly lacking, traditionally strong associations have been documented for beta-blockers, lithium, antimalarial drugs such as (hydroxy)chloroquine, interferons, imiquimod, and terbinafine. More recently, new associations have been reported for monoclonal antibody- and small-molecule-based targeted therapies used for oncological and immunological indications, such as tumor necrosis factor-alpha antagonists and anti-programmed cell death protein 1 immune checkpoint inhibitors. Recognizing potential drug-related psoriasis is of clinical relevance to allow an optimal management of psoriasis. However, in clinical practice, identifying medication-related exacerbations and induction of psoriasis can be challenging. The clinical and histopathological features of drug-provoked psoriasis may differ little from that of “classical” nondrug-related forms of psoriasis. In addition, the latency period between start of the medication and onset of psoriasis can be significantly long for some drugs. Assessment of the Naranjo adverse drug reaction probability scale could be used as a practical tool to better differentiate drug-related psoriasis. The first step in the management of drug-related psoriasis is cessation and replacement of the offending drug when deemed clinically possible. However, the induced psoriasis skin lesions may persist after treatment withdrawal. Additional skin-directed treatment options for drug-related psoriasis follows the conventional psoriasis treatment guidelines and includes topical steroids and vitamin D analogs, ultraviolet phototherapy, systemic treatments, such as acitretin, methotrexate, and fumaric acid esters, and biological treatments. Keywords: psoriasis, drug-induced, psoriasiform, cutaneous drug reaction, beta-blocker, lithium, monoclonal antibodies, small molecules